2001
DOI: 10.2174/1381612013397681
|View full text |Cite
|
Sign up to set email alerts
|

New Issues About Melatonin and its Effects on the Digestive System

Abstract: In human beings, melatonin is secreted in a cyclic way by the pineal gland, although it has been detected in other tissues. Synthesis of melatonin takes place in the pinealocyte. It depends on adrenergic stimulation, and its secretion is related to the photoperiod in a circadian model of low activity during light phase and high activity at night time. Former studies aimed to establish the mechanisms by which melatonin carries out its biological function, proved the existance of high affinity binding sites. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 144 publications
(182 reference statements)
0
32
0
2
Order By: Relevance
“…All these results lead us to suppose an endogenous melatonin synthesis in human thymus. In general, while pineal melatonin seems to act as a typical hormone in the organism, exerting an endocrine action reaching its target cells through the bloodstream, extrapineal melatonin may play intracrine, autocrine and paracrine key roles in those tissues where it is synthesized [23,37,53]. In this way, the resulting melatonin action on a tissue is the sum of the circulating melatonin action, most of which is of pineal origin, plus the endogenous melatonin action (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All these results lead us to suppose an endogenous melatonin synthesis in human thymus. In general, while pineal melatonin seems to act as a typical hormone in the organism, exerting an endocrine action reaching its target cells through the bloodstream, extrapineal melatonin may play intracrine, autocrine and paracrine key roles in those tissues where it is synthesized [23,37,53]. In this way, the resulting melatonin action on a tissue is the sum of the circulating melatonin action, most of which is of pineal origin, plus the endogenous melatonin action (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…38 Apart from its radical scavenging activity, melatonin is believed to exert a direct defence on the epithelium and to enhance submucosal blood flow. 11 It was reported that melatonin enhances microcirculation by cyclo-oxygenasederived prostaglandins and nitric oxide. 38 Moreover, the hormone is reported to stimulate the synthesis of gastroprotective hormones.…”
Section: Discussionmentioning
confidence: 99%
“…MEL administered in tap water is absorbed in gastrointestinal tract which itself is a source of synthesis and release of MEL in enterochrmaffin cells (Raikhlin and Kvetnoy 1976;Bubenik 1980). Gastrointestinal MEL regulates many physiological functions of digestion and nutrient absorption; its receptors in gastrointestinal tract have similar characteristics as MEL receptors in central nervous system (Motilva et al 2001). The fact remaining unclear is whether the MEL synthesis in gastrointestinal tract decreases with aging similarly to the MEL synthesis in epiphysis.…”
Section: Discussionmentioning
confidence: 99%